2017
DOI: 10.1016/j.jsams.2016.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent walking, but not standing, improves postprandial insulin and glucose relative to sustained sitting: A randomised cross-over study in inactive middle-aged men

Abstract: Interrupting sustained sitting with brief repeated bouts of light-intensity walking but not standing reduced insulin demand and improved glucose uptake during a simulated sedentary working day. The benefits of such minor behavioural changes could inform future workplace health interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
105
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(116 citation statements)
references
References 29 publications
7
105
3
1
Order By: Relevance
“…This finding adds to the existing evidence on the acute beneficial effects of regularly breaking up prolonged sitting with short bouts of light-intensity walking on blood glucose regulation. 1,2,3,5 However, our effect size is considerably larger compared with previous studies, which reported reductions in postprandial glycemia ranging from 9.0% 5 to 28.0%. 3 One possible reason for this could be the different methods used to measure glucose concentration.…”
Section: Discussioncontrasting
confidence: 67%
See 4 more Smart Citations
“…This finding adds to the existing evidence on the acute beneficial effects of regularly breaking up prolonged sitting with short bouts of light-intensity walking on blood glucose regulation. 1,2,3,5 However, our effect size is considerably larger compared with previous studies, which reported reductions in postprandial glycemia ranging from 9.0% 5 to 28.0%. 3 One possible reason for this could be the different methods used to measure glucose concentration.…”
Section: Discussioncontrasting
confidence: 67%
“…Two previous studies in adults without metabolic impairment reported no effect of standing. 1,5 However, the participants were younger and leaner than those in the current study and thus may have been more insulin sensitive. 20 These findings suggest that standing still for two minutes may only be a sufficient stimulus for insulin resistant individuals, with insulin sensitive individuals requiring longer standing bouts 10 or additional movement during the standing bouts.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations